Subcutaneous Connective Tissue Reaction to a New Nano Zinc-Oxide Eugenol Sealer in Rat Model - Omidi, Salma; Javidi, Maryam; Zarei, Mina; Mushakhian, Siavash; Jafarian, Amirhossein (Iranian Endodontic Journal, 2016)
Introduction: The aim of this animal study was to evaluate the histological response of the new nano zinc-oxide eugenol (NZOE) sealer in comparison with Pulp Canal Sealer (ZOE based) and AH-26 (epoxy resin sealer). Methods and Materials: A total of 27 Wistar rats were used. Four polyethylene tubes were implanted in the back of each rat (three tubes containing the test materials and an empty tube as a control). Then, 9 animals were sacrificed at each interval of 15, 30 and 60 days, and the implants were removed with the surrounding tissues.Samples were evaluated for the presence of inflammatory cell (mononuclear cell), vascular changes, fibrous tissue formation and present of giant cell. Comparisons between groups and time-periods were performed using the Kruskal-Wallis and Mann-Whitney U non-parametric tests. The level of significance was set at 0.05. Results: No significant difference was observed in tissue reactions and biocompatibility pattern of three sealers during 3 experimental periods (P<0.05). In all groups the tissue behavior showed tendency to decrease the irritation effect over time. Conclusion: The new nano zinc-oxide eugenol sealer has histocompatibility properties comparable to conventional commercial sealers. Keywords: Biocompatibility; Nanoparticle; Tissue Reaction; Zinc-Oxide Eugenol